2021
DOI: 10.3390/nano12010006
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun Methacrylated Gelatin/Poly(L-Lactic Acid) Nanofibrous Hydrogel Scaffolds for Potential Wound Dressing Application

Abstract: Electrospun nanofiber mats have attracted intense attention as advanced wound dressing materials. The objective of this study was to fabricate methacrylated gelatin (MeGel)/poly(L-lactic acid) (PLLA) hybrid nanofiber mats with an extracellular matrix (ECM) mimicking nanofibrous structure and hydrogel-like properties for potential use as wound dressing materials. MeGel was first synthesized via the methacryloyl substitution of gelatin (Gel), a series of MeGel and PLLA blends with various mass ratios were electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 48 publications
(68 reference statements)
0
11
0
Order By: Relevance
“…Although electrospun nanofibers made of pure gelatin have been successfully produced based on numerous different spinning solvents, the gelatin macromolecules in electrospun nanofibers commonly possess random coil conformation, inevitable resulting in inferior water-resistant capacity and poor mechanical properties. The previous studies demonstrated that the electrospun nanofibers made of pure gelatin may dissolve immediately once contacted with water [ 75 , 76 ]. To address these issues, lots of different physical or chemical crosslinking strategies have been developed to process the as-fabricated electrospun gelatin nanofibers [ 77 , 78 ].…”
Section: Electrospun Gelatin-based Nanofibersmentioning
confidence: 99%
See 2 more Smart Citations
“…Although electrospun nanofibers made of pure gelatin have been successfully produced based on numerous different spinning solvents, the gelatin macromolecules in electrospun nanofibers commonly possess random coil conformation, inevitable resulting in inferior water-resistant capacity and poor mechanical properties. The previous studies demonstrated that the electrospun nanofibers made of pure gelatin may dissolve immediately once contacted with water [ 75 , 76 ]. To address these issues, lots of different physical or chemical crosslinking strategies have been developed to process the as-fabricated electrospun gelatin nanofibers [ 77 , 78 ].…”
Section: Electrospun Gelatin-based Nanofibersmentioning
confidence: 99%
“…The final generated nanofiber mats had increased structural stability and great water uptaking capacity. Sun et al synthesized methacrylated gelatin (MeGel) through a methacryloyl substitution of gelatin ( Figure 4 B) [ 76 ]. The synthesized MeGel was blended with PLLA for electrospinning, and a subsequent UV crosslinking process was used to stabilize the MeGel component of MeGel/PLLA nanofiber mats ( Figure 4 C).…”
Section: Electrospun Gelatin-based Nanofibersmentioning
confidence: 99%
See 1 more Smart Citation
“…Nanomedicines also seem to aid healing through molecular and cellular pathways [75]. For example, a methacrylated gelatin (MeGel)/poly(L-lactic acid) hybrid nanofiber synthesised has been reported to stimulate the recruitment and proliferation of human dermal fibroblasts, thereby promoting wound healing [76]. Nanoparticles can not only act as carriers of antimicrobial agents, they can also have an intrinsic antimicrobial effect [75,77,78].…”
Section: Advanced Therapiesmentioning
confidence: 99%
“…Unfortunately, there are still no ideal strategies for the scarless regeneration and full recovery of diabetic wound in clinics [ 7 ]. The design and development of advanced dressing materials with multiple functions seem to be a promising strategy to address this intractable issue [ 8 ].…”
Section: Introductionmentioning
confidence: 99%